2015
DOI: 10.1016/j.heares.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Potassium ion channel openers, Maxipost and Retigabine, protect against peripheral salicylate ototoxicity in rats

Abstract: Sodium Salicylate (SS) reliably induces a sensorineural hearing loss and tinnitus when administered in high doses. Recent animal modeled studies indicate that potassium channel openers such as Maxipost and Retigabine (RTG) can block SS- or noise-induced tinnitus respectively; however, the origins and mechanisms are poorly understood. Since SS blocks the same potassium channels that Maxipost and RTG open, we postulated that these drugs might influence peripheral auditory function. To test this hypothesis Maxipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
2
23
0
1
Order By: Relevance
“…Moreover, application of KCNQ channel activators did not affect ABR thresholds, wave I amplitude, or PPI ratios ( Figure 7B–D , Figure 7—figure supplement 1B ), suggesting that these activators do not affect either noise-induced hearing threshold shifts or auditory nerve damage. These results are consistent with recent studies showing that application of retigabine does not have any effect on hearing thresholds ( Sheppard et al, 2015 ). However, application of retigabine reduced hearing loss in an animal model of sodium salicylate-induced sensorineural hearing loss and tinnitus ( Sheppard et al, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…Moreover, application of KCNQ channel activators did not affect ABR thresholds, wave I amplitude, or PPI ratios ( Figure 7B–D , Figure 7—figure supplement 1B ), suggesting that these activators do not affect either noise-induced hearing threshold shifts or auditory nerve damage. These results are consistent with recent studies showing that application of retigabine does not have any effect on hearing thresholds ( Sheppard et al, 2015 ). However, application of retigabine reduced hearing loss in an animal model of sodium salicylate-induced sensorineural hearing loss and tinnitus ( Sheppard et al, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…Immediately after acquiring the IC data, the CAP and SP were collected from the cochlea as described previously (Chen, Stolzberg et al 2013, Sheppard, Chen et al 2015). The animal was placed in a customized head-holder, the right bulla was exposed and a small fistula made to access the cochlear round window.…”
Section: Methodsmentioning
confidence: 99%
“…[10] A comparison of Maxipost and retigabine in rats with salicylate-induced hearing loss revealed that Maxipost prevented hearing loss at high frequencies, whereas retigabine prevented hearing loss at low frequencies. [11] These effects seem to be mediated by potassium channels in the cochlea, since Maxipost and retigabine have a differential effect on Kv7 and BK potassium channels and since the expression of these channels varies on the cochlear hair cells along the tonotopic gradient. [11] In another recent study ICA-105665, a novel small molecule that opens Kv7.2/3 and Kv7.3/5 channels, has been investigated in rats.…”
Section: Kv7 (Kcnq) Potassium Channelsmentioning
confidence: 99%
“…[11] These effects seem to be mediated by potassium channels in the cochlea, since Maxipost and retigabine have a differential effect on Kv7 and BK potassium channels and since the expression of these channels varies on the cochlear hair cells along the tonotopic gradient. [11] In another recent study ICA-105665, a novel small molecule that opens Kv7.2/3 and Kv7.3/5 channels, has been investigated in rats. [12] Hearing reduction after salicylate application could be prevented by ICA-105665 and it was hypothesized that it may also be effective in the prevention of salicylate-induced tinnitus.…”
Section: Kv7 (Kcnq) Potassium Channelsmentioning
confidence: 99%